Molecular Dynamics Simulation of the Effects of Methane Hydrate Phase Transition on Mechanical Properties of Deep-Sea Methane Hydrate-Bearing Soil - Yanmei Zhang; Jian Zhang; Guoxun Li; Changda Sun; Yalin Luan; Jianlin Liu (Advances in Civil Engineering)
In this paper, the methane hydrate phase transition process in deep-sea methane hydrate-bearing soil under heating and compression was simulated by the molecular dynamics method. The evolution of deep-sea methane hydrate-bearing soil’s microstructure, system energy, intermolecular interaction energy, and radial distribution function during heating and compression was investigated. The micromechanism of the influence of the methane hydrate phase transition on the mechanical properties of deep-sea methane hydrate-bearing soil was analyzed. The results demonstrated that the methane hydrate dissociation starts from both sides to the middle and the void spaces between the soil particles had nearly no change during the heating process. For the compression process, the methane hydrate on both sides and the middle dissociated at the same time, and the void spaces became smaller. The methane hydrate phase transition on the effects of mechanical properties of the deep-sea methane hydrate-bearing soil is mainly caused by three aspects. (1) the dissociation of methane hydrate incurs the decrease of methane hydrate saturation. The free water and methane molecules generated cannot migrate in time and thus lead to the increase of excess pore water press and excess pore gas press. (2) The dissipated energy causes the decrease of the effective stress between the soil particles. (3) Due to the methane hydrate decomposition, the free water molecules increase, which reduces the friction of soil particles.